Orçamento detalhado de uma edificação de uso misto – um estudo de caso - Lacerda, Adaiana Felipe de (Universidade Federal Rural do Semi-Árido, 2019)
The budget is one of the activities of major importance for the execution of any project, making feasible or not its realization. It is through it that it is possible to quantify all the services and inputs (materials, labor and equipment) necessary for the execution of the enterprise. According to the literature, even if very detailed is only an approximation of the real cost. Therefore, in order to approximate the real resource that will be necessary for the execution, a complete and detailed project is essential, a descriptive memorial specifying the categories of materials to be used, which leaves no doubt as to the execution procedures. Thus, the objective of this work is the construction of a budget for a mixed-use building (commercial and residential), based on the definition of the constructive methodology, and subsequently the quantification of services and appropriation of the SEINFRA indexes. The price reference system adopted) for the preparation of the budget worksheet and, finally, the comparison of the result obtained with the CUB (basic unit cost of construction). As a methodology, the bibliographical and documentary researches were carried out in order to obtain the theoretical basis necessary for the design of the work. In addition, a case study was carried out, taking as object of study a project of a mixed construction, obtaining the detailed budget, the curve ABC or Pareto (where it is possible to verify which are the inputs of greater impact, and thus serve as a tool for decision-making that contributes to decrease the total cost of the enterprise, seeking to economise precisely on these inputs) and later the comparison with the CUB. In this way, it was concluded that according to the whole calculation of the services quantitative, taking into consideration the adopted compositions, the value necessary to carry out the work is R$ 493,966.78. Already estimated value for the cost of construction of the property from the CUB is R$ 357,968.64. It is concluded that the budget is a significant instrument for the consummation of the work successfully and it is necessary a careful calculation of all the details of the projects, since each work has its particularities
Keywords: Orçamento; Custo unitário básico da construção; Curva ABC; Budget; Basic unit cost of construction; ABC curve; ENGENHARIAS::ENGENHARIA CIVIL